2017
DOI: 10.1002/anie.201610918
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of a Chiral Imine Molecular Switch Followed by Matrix‐Isolation VCD Spectroscopy

Abstract: Characterizing the stereochemistry of transient photoisomerization products remains a big challenge for the design of molecular machines, such as unidirectional molecular motors. Often these states are not stable long enough to be characterized in detail using conventional spectroscopic tools. The structurally simple camphorquinone imine 1 serves to illustrate the advantage of combining the matrix-isolation technique with vibrational circular dichroism (VCD) spectroscopy for the investigation of photoisomeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…These results indicate the different disposition of the p ‐tolyl groups in the ( S , S )‐ 3 :Ag 3 complex compared with that in the other complexes. These experimental results represent one of the very scarce examples of VCD switches reported to date …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These results indicate the different disposition of the p ‐tolyl groups in the ( S , S )‐ 3 :Ag 3 complex compared with that in the other complexes. These experimental results represent one of the very scarce examples of VCD switches reported to date …”
Section: Resultsmentioning
confidence: 94%
“…These resultsi ndicate the different disposition of the p-tolyl groups in the (S,S)-3:Ag 3 complexc ompared with that in the other complexes.T hese experimental results repre- sent one of the very scarce examples of VCD switches reported to date. [48] Theoretical studies on o-OPE:Ag I complexes To better understanda ll of theseo bservations, we carried out theoretical calculations for the Ag I complexes of o-OPE ligands (S,S)-1-8.F or (S,S)-1,t heoretical calculations revealed that the more favorable situation corresponded to silver coordinated between the alkyne and OMe (Figure 9), in which both ÀOMe groups wereoriented to the Ag + ion, leading to ahighly stabilizing interaction. The systemi ns uch ad isposition adopted an anti conformation.…”
Section: Cpl and Vcd Studiesmentioning
confidence: 99%
“…Couplets in particular were enhanced due to the increased resolution. This method is having a renaissance, with Vass, Xu, Merten and co-workers using improved instrumentation and reporting studies of propylene oxide, methyl lactate, and small alcohols correlated with spectral simulations to determine structures of isolated molecules or of their complexes in the matrix [ 110 , 111 , 112 ].…”
Section: Comparison Of Methodsmentioning
confidence: 99%
“…23 We recently published a survey on different computational tools to describe conformational sampling. 24 Typically, VCD is measured in liquid state or in or in isolated conditions such as noble gas matrices, [26][27][28][29][30] which is a largely standardised procedure, but requires sample solubility and may exhibit spurious solvent effects. However, in analogy to IR absorption, VCD can also be measured conveniently in solid state.…”
mentioning
confidence: 99%